Fossil associations from the middle and upper Eocene strata of the Pamplona Basin and surrounding areas (Navarre, western Pyrenees) - Astibia, Humberto; Payros, Aitor; Ortiz, Silvia; Elorza, Javier; Álvarez-Pérez, German; Badiola, Ainara; Bardet, Nathalie; Berreteaga, Ana; Calzada, Sebastián; Corral, José Carmelo; Díaz-Martínez, Ignacio; Merle, Didier; et al. (Journal of Iberian Geology, 2016)
Fossil associations from the middle and upper Eocene (Bartonian and Priabonian) sedimentary succession of the Pamplona Basin are described. This succession was accumulated in the western part of the South Pyrenean peripheral foreland basin and extends from deep-marine turbiditic (Ezkaba Sandstone Formation) to deltaic (Pamplona Marl, Ardanatz Sandstone and Ilundain Marl formations) and marginal marine deposits (Gendulain Formation). The micropalaeontological content is high. It is dominated by foraminifera, and common ostracods and other microfossils are also present. The fossil ichnoasssemblages include at least 23 ichnogenera and 28 ichnospecies indicative of Nereites, Cruziana, Glossifungites and ?Scoyenia-Mermia ichnofacies. Body macrofossils of 78 taxa corresponding to macroforaminifera, sponges, corals, bryozoans, brachiopods, annelids, molluscs, arthropods, echinoderms and vertebrates have been identified. Both the number of ichnotaxa and of species (e. g. bryozoans, molluscs and condrichthyans) may be considerably higher. Body fossil assemblages are comparable to those from the Eocene of the Nord Pyrenean area (Basque Coast), and also to those from the Eocene of the west-central and eastern part of South Pyrenean area (Aragon and Catalonia). At the European scale, the molluscs assemblages seem endemic from the Pyrenean area, although several Tethyan (Italy and Alps) and Northern elements (Paris basin and Normandy) have been recorded. Palaeontological data of studied sedimentary units fit well with the shallowing process that throughout the middle and late Eocene occurs in the area, according to the sedimentological and stratigraphical data.